Safety of pediatric patients in the use of medicines in the Intensive Care Unit (Research, Society and Development, 2022)
The general objective of the study is to analyze through the literature the main aspects of pediatric patient safety in the use of medicines in the ICU. The study was carried out through a literature review. As for the approach, it is classified as qualitative. Patient safety in the pediatric ICU related to medication administration also includes procedures for the prevention and control of infections, through hand washing before and after performing the procedures. In addition, it is noteworthy that the nursing team, when administering medications, must consider institutional safety protocols to prevent adverse events. It is noticed that patient safety is of paramount importance for patient care, together with the multiprofessional health team, where this professional promotes patient safety and the effectiveness of pharmacotherapy through the identification, resolution and prevention of problems that are related to the drugs administered.